Training the Creative Librarian in the Age of Technological Advancement - D., Onuoha Uloma; ., Ukachi Ngozi (Information Management and Business Review, 2013)
This paper examined the changes in librarianship brought about by advancement in technology especially as it relates to new work functions expected of librarians. The major objective of the study was to identify the role of curriculum in the training of creative and innovative librarians. The paper demonstrates that curriculum re-assessment in library schools is necessary for the mastery of knowledge needed for problem solving on which the basis of creativity and innovation lies. As a result, the paper concludes by recommending amongst others, that the curriculum of library schools be reviewed taking into consideration the current job requirements of librarians as this would empower librarians apply knowledge to problem solving, thereby bringing about creativity and innovation in library services. Library administrators should also encourage innovation and creativity by ensuring an enabling environment where staff is free to experiment with technology without fear of reproof.